The Linguistic Taboo between Malays and Ibans of Sarawak, Malaysia - Morni, Affidah; Johari, Aiza; Ahmad, Johnny; Jusoff, Kamaruzaman (2009)
This study attempts to determine the Malays’ and Ibans’ perceptions on the use of linguistic taboo in their culture based on the specified domains and to investigate the occurrence of linguistic taboo in different domains. The outcome of this study would provide a useful understanding over the Malays’ and Ibans’ sensitivity over the usage of certain words which are considered taboo in their community. Hence, avoid occurrences of embarrassment or offensiveness by the speakers. Questionnaires were given to 40 Sarawak Malays and 40 Ibans of varying educational background and age in Kuching area. They were selected randomly based on convenience random sampling and the data were analyzed using SPSS 10.0. The findings show that many respondents believed that taboo words should not be spoken publicly or openly where certain topics should not be discussed in candid especially in relation to sex, body parts, bodily functions, death and dying. Nonetheless, the cultural norms, rules and the notion of politeness (and among the Malays the tenets of religion) play significant roles in restricting the open use of these taboo words either behaviourally or linguistically. Comparatively, the Iban respondents seemed to be more expressive and candid in using taboo words in expressing their emotions, as compared to the Malays. It is also apparent that the use of taboo words can be acceptable depending on the domains and contexts.